Effects of thickness and polishing treatment on the translucency and opalescence of six dental CAD-CAM monolithic restorative materials: an in vitro study - Zhengda Wu; Jiehua Tian; Donghao Wei; Yifan Zhang; Ye Lin; Ping Di (BMC, 2023)
Abstract Background Computer-aided design and computer-aided manufacturing (CAD-CAM) materials for prosthetic is gaining popularity in dentistry. However, limited information exists regarding the impact of thickness and roughening treatment on the optical properties of contemporary CAD-CAM restorative materials. This study aimed to quantitatively evaluate the translucency and opalescence of six dental CAD-CAM materials in response to different thicknesses and roughening treatments. Methods Six dental CAD-CAM materials, lithium disilicate glass-ceramic (IPS e.max CAD, LS), polymer-infiltrated ceramic (VITA Enamic, VE), resin-nano ceramic glass-ceramic (LAVA Ultimate, LU), polymethyl methacrylate (Telio CAD, TE), and two zirconia reinforced lithium silicate (VITA Suprinity, VS, and Celtra Duo, CD), in shade A2 were prepared as 12 × 12mm2 specimens of four thicknesses (0.5mm, 1.0mm, 1.5mm, and 2.0mm) (N = 240, n = 10). After three different treatments (polished, roughened by SiC P800-grit, and SiC P300-grit), the translucency parameter (TP00) and opalescence parameter (OP) were measured with a spectrophotometer (VITA Easyshade V). The surface roughness was analyzed with a shape measurement laser microscope. The data were analyzed using a MANOVA, post hoc Tukey-Kramer test, the t test, and regression analysis (α = .05). Results The TP00 and OP were significantly influenced by material type, thickness and roughening treatment (P < .05). TP00 showed a continues decline with increasing thicknesses, while the variations of OP were material-dependent. TP00 ranged from 37.80 (LS in 0.5mm) to 5.66 (VS in 2.0mm), and OP ranged from 5.66 (LU in 0.5mm) to 9.55 (VS in 0.5mm). The variations in TP00 of all materials between adjacent thicknesses ranged from 2.10 to 15.29, exceeding the acceptable translucency threshold except for LU. Quadratic and logarithmic regression curves exhibited the best fit for TP00 among the materials. Compared to polished specimens, rougher specimens exhibited lower TP00 and higher OP in all materials except for LS (P < 0.05). Roughening with P300-grit decreased TP00 and OP by an average of 2.59 and 0.43 for 0.5mm specimens, and 1.26 and 0.25 for 2.0mm specimens, respectively. Conclusions Variations in translucency caused by thickness and roughening treatment were perceptible and may be clinically unacceptable. Careful consideration should be given to the selection of CAD-CAM materials based on their distinct optical properties.